Nudity and eroticism in movement: Exploring the dimensions of the body in stage dance (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article analyzes the relationship between eroticism and the naked body in stage dance. It began its investigation by exploring the confrontation between the 'erotic-body' and the 'non-erotic-body', breaking down four approaches: 'nude-attenuated', 'nude-emulated', 'nude-partial' and 'nude-integral'. During this process, the influences of currents such as postmodern dance were examined, highlighting their role in the dissociation between nudity and eroticism. In addition to exploring the complexity of the body in movement, the article provides tools for choreographic analysis and proposes research methods that incorporate subjectivity in scenic dance.
Keywords: choreography; body; dance; nudity; eroticism